Histopathological, histochemical and biochemical postmortem changes in induced fatal hypothermia in rats - Mahrous Abdelbasset Ibrahim; Sally Salem Mohammed; Hany Goda Tammam; Rehab Ibrahim Abdel-Karim; Medhat Mohammed Farag (Oxford University Press, 2021)
Reaching a postmortem diagnosis of hypothermia is challenging in forensic practice. Therefore, this study was conducted to detect the histopathological, histochemical and biochemical changes that occur in adult albino rats following exposure to induced fatal hypothermia. Twenty-four adult albino rats were divided into the negative control, moderate hypothermia, severe hypothermia and hypoxia groups. Rats in the control group were euthanized when those in the moderate hypothermic group died. Blood samples were collected via heart puncture, and the cerebrum, heart, suprarenal gland, kidney, liver and skeletal muscle were removed to investigate the biochemical, histochemical and histopathological changes. Postmortem assessment depicted significant changes in lipid peroxidation, represented by increased malondialdehyde levels in the studied organs of the rats in hypothermic and hypoxia groups. Histopathological examination of the rats' organs revealed degeneration and necrosis in the hypothermia and hypoxia groups. Sections taken from the severe hypothermic rats revealed a loss of normal cardiac tissue architecture, necrotic changes in the pyramidal cells in the cerebral cortex, and massive necrosis, mainly in the tubules of the renal cortex and medulla. These findings suggest that histological changes might be used as biochemical markers for postmortem diagnosing of fatal hypothermia, particularly in severe hypothermic conditions. Key points Death by hypothermia is a serious public health problem worldwide. Confirming a diagnosis and determining the cause of death in cases of hypothermia are among the most difficult practices in forensic medicine. Death by hypothermia might be associated with structural abnormalities in various organs. Studies using different tissue staining techniques will enable an overall illustration of the role of histopathological changes in body organs as indicators of hypothermia.